An Indigenous Soil Bacterium Facilitates the Mitigation of Rocky Desertification in Carbonate Mining Areas. (30th June 2017) - Wu, Yanwen; Zhang, Jinchi; Guo, Xiaoping
Abstract: Carbonate minerals are extensively distributed across China, and their special rock structures make them vulnerable to land damage through mining, leading to rocky desertification. Soil microorganisms play an important role in mineral weathering. However, little is known about the utilization of the mineral‐weathering microorganisms to alleviate the problem of rocky desertification in mines. In the present study, the mineral‐solubilizing bacterium NL‐11 was isolated from soil around weathered dolostones and identified as Bacillus thuringiensis based on the Biolog identification system and 16S rDNA sequence analysis. The mineral dissolution experiments revealed that inoculation with the live bacterium significantly increased the mineral sample dissolution via significantly enhancing Ca and Mg release, with increase values of 303·27 and 50·55 mg L −1 respectively, compared with that with the inactivated bacterium. Moreover, the acetic acid secreted by strain NL‐11 markedly decreased the size of particle diameter (quantified with a laser diffraction particle size analyser) through reducing pH value. The eroded traces were observed by scanning electron microscopy analysis, and the results further verified the erosional effects of this strain. In addition, this bacterium contributed to the establishment and proliferation of plants by providing nutrient elements, such as phosphorus (P) and potassium (K). Our study not only provided an efficient bacterial strain NL‐11 but also enriched the technologies to mitigate problems associated with ecological restorations of carbonate mines. Copyright © 2017 John Wiley & Sons, Ltd.